Pengaruh Penambahan Pasir Pantai Pada Tanah Dengan Uji Dynamic Cone Penetrometer - Imanuel Ali Nur Sinala Amaral; Irwan Lie Keng Wong; Helen A.I. Sopacua (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
This study was intended to determine the effect of adding beach sand to clay soil on the Dynamic Cone Penetrometer (DCP) test. The methodology in this research is testing soil characteristics, composition of the Proctor Standard test mixture and Dynamic Cone Penetrometer testing. The results showed that the soil met the characteristics of a clay soil. From the Proctor Standard test on a mixture variation of 0%, 7%, 14%, 21%, there was an increase in the optimum moisture content and the maximum dry density. From the Dynamic Cone Penetrometer (DCP) test, the CBR value increased at each additional variation from 0% to 21%. Beach sand increases the CBR value of the soil so that it can be used to increase the bearing capacity of clay soil.